Africa's struggle for its art history of a postcolonial defeat - Savoy, Bénédicte 1972- (Princeton University Press, 2022)
A major new history of how African nations, starting in the 1960s, sought to reclaim the art looted by Western colonial powers For decades, African nations have fought for the return of countless works of art stolen during the colonial era and placed in Western museums. In Africa's Struggle for Its Art, Bénédicte Savoy brings to light this largely unknown but deeply important history. One of the world's foremost experts on restitution and cultural heritage, Savoy investigates extensive, previously unpublished sources to reveal that the roots of the struggle extend much further back than prominent recent debates indicate, and that these efforts were covered up by myriad opponents.Shortly after 1960, when eighteen former colonies in Africa gained independence, a movement to pursue repatriation was spearheaded by African intellectual and political classes. Savoy looks at pivotal events, including the watershed speech delivered at the United Nations General Assembly by Zaire's president, which started the debate regarding restitution of colonial-era assets and resulted in the first UN resolution on the subject. She examines how German museums tried to withhold information about their inventory and how the British Museum Act, which protected British collections, came under fire in the House of Lords, but a proposed amendment to the act did not prevail. Savoy concludes in the mid-1980s, when African nations enacted the first laws focusing on the protection of their cultural heritage.Making the case for why restitution is integral for any future relationship between African countries and the West, Africa's Struggle for Its Art will shape conversations around these crucial issues for years to come